Modern tourism in global perspective - Collins, Thaddens (London, United Kingdom Vintage Press Ltd, 2023)
"This book discuss about various types of tourism. It also included various World Heritage Sights." --
The Era of Popular Tourism: 1950 to the 21st Century, 2. The Hospitality Sector, 3. Sustainable Tourism in Modern World, 4. New Trends in Tour Packages, 5. Package Holiday and Aviation Industry, 6. Travel Agency and Tour Operators, 7. Tourism as a Geographical Phenomenon, 8. Nature Based Tourism in the World, 9. Tourism as a Development Strategy, 10. Tourism in an International Context
Includes bibliographical references and index.
Keywords: Tourism; Tourism -- Planning